2004
DOI: 10.1021/la048173f
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Synthesis of Layered Manganese Oxides Intercalated with Tetraalkylammonium Ions

Abstract: Thin films of birnessite-type layered manganese oxides with various interlayer spacings have been prepared on a platinum electrode by a one-step electrochemical procedure. The process involves a potentiostatic oxidation of aqueous Mn(2+) ions at around +1.0 V (Ag/AgCl) in the presence of tetraalkylammonium cations with different alkyl chain lengths. X-ray diffraction indicates that the films deposited with tetrabutylammonium (TBA), tetrapropylammonium (TPA), and tetraethylammonium (TEA) ions are composed of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
113
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(124 citation statements)
references
References 37 publications
11
113
0
Order By: Relevance
“…Similar morphology has been observed for plate-like layered manganese oxide catalysts [22][23][24]; however, the larger surface area in these studies was probably caused by the presence of pillared material (e.g., alumina, lithium). The presence of pillared material creates a larger interlayer distance and results in pores having the form of parallel plates.…”
Section: Scanning Electron Microscopysupporting
confidence: 81%
“…Similar morphology has been observed for plate-like layered manganese oxide catalysts [22][23][24]; however, the larger surface area in these studies was probably caused by the presence of pillared material (e.g., alumina, lithium). The presence of pillared material creates a larger interlayer distance and results in pores having the form of parallel plates.…”
Section: Scanning Electron Microscopysupporting
confidence: 81%
“…The peak binding energy (BE) values of Mn 2p 3=2 spectra are within 641.5-642.1 eV. According to literature reports, [24][25][26][27] cations with sufficient coverage to the IrO 2 substrate seems to be responsible for high oxygen evolution efficiency and high activity of the deposits during seawater electrolysis. Table 1 summarizes changes in composition, current efficiency of manganese deposition, thickness, grain size for oxide deposits and mass% of structural water with change in concentration and pH of the deposition electrolytes.…”
Section: Phyiscochemical Characterizationmentioning
confidence: 79%
“…The thus-prepared layered MnOx consists of negatively charged MnOx layers and Et4N cations sandwiched between them, as described in our previous paper. 5 The layered structure is substantially the same as those of alkylammonium/ MnOx materials prepared chemically by other researchers. 11,12 As shown in Fig.…”
Section: Incorporation Of Mb Into Electrodeposited Mnox Filmmentioning
confidence: 55%
“…4 The process involves an anodic oxidation of aqueous Mn 2+ ions in the presence of the corresponding guest cations. Our preliminary studies indicated that the bulky organic cations incorporated during electrodeposition are replaceable with smaller alkaline metal ions 5 or methylene blue 6 by ion-exchange. In the present study, the sorptive properties of layered manganese oxide film grown electrochemically toward methylene blue [MB, (CH3)2N(C6H3)-NS + (C6H3)N(CH3)2] were examined in detail in aqueous solutions with and without alkaline metal ions.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation